Comprehensive structured review of implementing flipped classroom approaches in education - Mazlan, Rohaida; Mahamod, Zamri; Jamaluddin, Khairul Azhar (Journal of Education and Learning (EduLearn), 2025)
In recent years, the flipped classroom model has garnered significant attention in education, marking a shift from conventional teaching methods to a more student-centered approach. This systematic review delves into the implementation of flipped classrooms and their influence on educational environments. The focus is on effective teaching strategies that enhance student engagement and learning outcomes. A detailed analysis of current research identifies common methodologies, such as using pre-recorded lectures and active learning techniques in class. Evidence suggests that flipped classrooms contribute to improved academic performance, increased student participation, and higher satisfaction levels. This review involved an extensive search of scholarly articles from databases like Scopus, Web of Science (WoS), and ERIC, covering studies published between 2021 and 2024. Using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework, 35 primary studies were analyzed, revealing three main themes: i) the effectiveness of blended learning, ii) flipped classroom methodologies and their impacts, and iii) technological innovations and gamification in education. In conclusion, the flipped classroom model shows promise for enhancing language education through more effective and engaging instructional methods. However, successful adoption requires careful planning and support to overcome potential challenges. This review offers valuable insights for educators and policymakers interested in innovative teaching approaches in language education.